The Risk Observatory: Developing an Aviation Safety Information Sharing Platform in Europe - Verstraeten, J.; Baren, G.B. van; Wever, R. (Macrothink Institute, 2016)
In Europe the accident rate in commercial aviation has stagnated at around 40 accidents per ten million flights: forty times higher than Europe’s ambition. Currently safety management is done per organisation, focusing on an organisation’s own domain. European research institutions and the aviation sector have joined their expertise in the EU-funded Future Sky Safety Programme. One project within the programme aims to enable inter-organisation and inter-domain safety management. The four year project will deliver a tool, the Risk Observatory, which acquires safety data and translates it into actionable safety information. In the first year, more than 20 European stakeholder organisations have been consulted to express their needs for a Risk Observatory. The resulting requirements have been used to develop an early prototype: mock-ups of dashboards and a user interface. The Risk Observatory has four main elements. (1) Tracking of safety performance indicators distilled from input safety data. (2) Trend diagrams and visualisations of accident risk. Risk models will be developed to translate the input data into accident risk. The risk models also allow (3) assessment of the effects of mitigation measures. There is added value in sharing qualitative safety knowledge, such as identified hazards, therefore, (4) a searchable repository is included. The early prototype is successfully used to validate and further specify the requirements. The need for inter-organisation and inter-domain safety data dissemination was confirmed by the stakeholders. In the coming years the project will develop a fully functional prototype risk observatory, risk models and a business model.
Keywords: Flight safety